2012
DOI: 10.1051/epjconf/20122900038
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PZT powder by conventional method at various conditions

Abstract: Abstract. In this work, the formation of Pb(Zr 1-x Ti x )O 3 solid solutions with composition near the morphotropic phase boundary (MPB) using the conventional ceramic method have been studied by changing the thermal conditions such as temperature ramp rate and isothermal times during the calcination treatment performed between 700 and 900 °C. (abbreviated PZT-PGMNNS) specimens have been examined by powder X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier Transform Infrared (FTIR) while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Further, the XRD patterns of the prepared pure PZT particles can easily be indexed with a reference pattern for PZT (JCPDS card nos. 73–2022 and 33–0748) where both rhombohedral (200) and tetragonal perovskite structure (002) and (200) co‐exist, while 2θ values 28.9° correspond to the pyrochlore phase . Besides, the XRD patterns of PVA–PZT composites (with 10 wt %) indicate no differences than the XRD patterns of pure PZT.…”
Section: Resultsmentioning
confidence: 95%
“…Further, the XRD patterns of the prepared pure PZT particles can easily be indexed with a reference pattern for PZT (JCPDS card nos. 73–2022 and 33–0748) where both rhombohedral (200) and tetragonal perovskite structure (002) and (200) co‐exist, while 2θ values 28.9° correspond to the pyrochlore phase . Besides, the XRD patterns of PVA–PZT composites (with 10 wt %) indicate no differences than the XRD patterns of pure PZT.…”
Section: Resultsmentioning
confidence: 95%
“…PZT has a perovskite structure, with Zr and Ti ions randomly placed on the edge of cell boundary sites. When used at 50% mol PbTiO 3 , this structure is referred to as the morphotropic phase boundary (MPB) [ 7 ], whose condition between the tetragonal and rhombohedral phases was explained by the composition–temperature diagram [ 8 , 9 ]. The coexistence of the tetragonal-rhombohedral phases in the PZT ceramic disk showed that the piezoelectric properties were higher when close to the boundary sites [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on solid precursors, the solid-state reaction (SSR) has been applied in the synthesis of PZT materials due to its simplicity. The temperature of this process also determined the characteristics of the synthesized PZT, such as crystallinity and particle sizes [ 9 , 16 ]. This involves a long duration, approximately 12–48 h, of the mechanical pre-mixing precursor process, such as a wet/dry ball-milling, to obtain more homogenous and finer particles [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to searching for new types of multiferroic materials, an intensive search for effective technological methods for their production (synthesis and sintering) to meet these unique requirements has been underway [ 1 , 4 ]. Numerous synthesis methods of ceramic materials are known, e.g., solid-state reaction technique [ 5 , 6 , 7 , 8 ], calcination [ 9 , 10 , 11 , 12 , 13 ], sol-gel [ 14 , 15 ], gel-combustion [ 16 ], mechanochemical activation [ 17 , 18 , 19 , 20 ], and the self-developing synthesis of SHS [ 21 , 22 ], as well as sintering methods, e.g., free sintering (pressureless sintering) [ 23 ], hot pressing [ 24 , 25 , 26 ], microwave sintering [ 23 , 27 , 28 ], spark plasma sintering SPS [ 29 , 30 , 31 , 32 ], and cold-sintering-assisted sintering CSS [ 33 , 34 ]. Well-known methods of synthesis and sintering are used to improve the functional properties of multiferroic materials, which are appropriately modified and combined in the technological process.…”
Section: Introductionmentioning
confidence: 99%
“…The best-known and widely used material with ferroelectric and piezoelectric properties is the solid solution Pb(Zr 1- x Ti x )O 3 (PZT) which is most often obtained with a solid-state reaction technique [ 5 , 6 ]. The properties of this material mainly depend on the Zr/Ti content ratio.…”
Section: Introductionmentioning
confidence: 99%